2018
DOI: 10.1016/j.expthermflusci.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Measuring turbocharger compressor inlet backflow through particle image velocimetry

Abstract: An experimental measurement campaign is presented where particle image velocimetry (PIV) was used in an effort to characterize the velocity field in a turbocharger compressor when unstable operating conditions lead to flow reversing from the diffuser into the inlet pipe. Previous studies have successfully used this and similar techniques, but the most relevant results have been obtained in an open compressor where the backflow can diffuse into the ambient. In this work a glass pipe long enough to confine the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Kugimoto et al adopted a one‐dimensional analytical model to predict the performance of a novel heat pump system that used a multistage Knudsen compressor, and they found that a heat pump system with a 30‐stage Knudsen compressor can yield an output power of 1.27 kW . Torregrosa et al observed the velocity field and identified the reversed flow in a turbocharger compressor by using particle image velocimetry (PIV), and they pointed out that the results agreed well with existing numerical predictions. Gancedo et al described the compressor stability and surge line of a turbocharger centrifugal compressor, and they emphasized that the surge limit criterion definition is significant for the actual surge margin improvement.…”
Section: Introductionmentioning
confidence: 82%
“…Kugimoto et al adopted a one‐dimensional analytical model to predict the performance of a novel heat pump system that used a multistage Knudsen compressor, and they found that a heat pump system with a 30‐stage Knudsen compressor can yield an output power of 1.27 kW . Torregrosa et al observed the velocity field and identified the reversed flow in a turbocharger compressor by using particle image velocimetry (PIV), and they pointed out that the results agreed well with existing numerical predictions. Gancedo et al described the compressor stability and surge line of a turbocharger centrifugal compressor, and they emphasized that the surge limit criterion definition is significant for the actual surge margin improvement.…”
Section: Introductionmentioning
confidence: 82%
“…3 shows a schematic representation of the laser PIV system. In this study, a standard 2D PIV system by TSI has been selected to measure 2D instantaneous velocity fields following the validated methodology presented by Torregrosa et al [31] and Pastor et al [32]. This involves a 15 Hz flashlamp pumped Nd:YAG laser with 135 mJ/pulse at 532 nm.…”
Section: Laser Piv Measurementsmentioning
confidence: 99%
“…For this purpose, oil droplets of 1 µm of diameter are supplied to the flow using an atomizer. A commercial synthetic oil based on liquid paraffin and isopropyl palmitate is employed, in accordance with the work of Torregrosa et al [31].…”
Section: Laser Piv Measurementsmentioning
confidence: 99%
“…The results presented in that work provide a valuable benchmark for comparing the compressor results with different inlet geometries. For compressor c2, PIV measurements of the inlet flow field are available only on the 140 krpm line [66]. In addition, the mass flow and pressure ratio values on that line are very similar to those on the 160 krpm line of compressor c1, facilitating the comparison between both.…”
Section: Studied Configurationsmentioning
confidence: 99%
“…A section of glass duct was placed in the experimental setup, and a longitudinal laser sheet was used to measure the axial velocity. The experimental setup and the measurement method are described in detail in [66].…”
Section: Validation Of Compressor C2mentioning
confidence: 99%